Study of the influence of Zr on the mechanical properties and functional response of Ti-Nb-Ta-Zr-O alloy for orthopedic applications. (15th February 2019) - Acharya, Srijan; Panicker, Arpana Gopi; Laxmi, Devara Vijaya; Suwas, Satyam; Chatterjee, Kaushik
Abstract: In Ti-Nb-Ta-Zr based β-titanium alloys intended for orthopedic applications, Zr does not affect the stability of low modulus β-phase, unlike Nb and Ta. The present study attempts to investigate the influence of Zr on the overall mechanical and functional responses of a Ti-Nb-Ta-Zr-O alloy in contrast to a new Ti-Nb-Ta-O alloy. In each material, different crystallographic textures were produced by varying the processing route. While both alloys were found to show low elastic modulus values due to their β-only microstructures, Ti-Nb-Ta-O alloy had lower elastic modulus because of its favorable crystallographic orientation caused by absence of Zr. The tensile strength values were remarkably high for both due to the presence of interstitial oxygen. The hardening effect of Zr was also evident from the higher strength of Ti-Nb-Ta-Zr-O as compared to Ti-Nb-Ta-O alloy. Although the corrosion resistance and in vitro biological behavior of the two alloys were satisfactory, the Ti-Nb-Ta-Zr-O alloy showed lower corrosion rate and improved osteoblast attachment than the Ti-Nb-Ta-O alloy. Thus, whereas the two alloys show promising performance in terms of their mechanical and functional response, presence of Zr marginally improves the performance in the Ti-Nb-Ta-Zr-O for orthopedic applications. Graphical abstract: Highlights: A low modulus Ti-34Nb-2Ta-0.5O alloy with a microstructure similar to that of Ti-34Nb-2Ta-3Zr-0.5O was developed. The presence of oxygen stabilized β-phase and caused significant interstitial solid solution strengthening in both alloys. The difference in texture between the two alloys resulted in lower elastic modulus of Ti-34Nb-2Ta-0.5O. Presence of Zr in Ti-34Nb-2Ta-3Zr-0.5O improved both its tensile strength and corrosion resistance. In vitro studies with osteoblasts revealed good cellular response to both the alloys.